Identification of class 1 and 2 integrons from clinical and environmental Salmonella isolates - Corrêa, Fábio Ederson Lopes; Dantas, Fabiana Gomes da Silva; Grisolia, Alexeia Barufatti; Crispim, Bruno do Amaral; Oliveira, Kelly Mari Pires (The Journal of Infection in Developing Countries, 2014)
Introduction: The indiscriminate use of antimicrobials has selected for the emergence of resistant strains. Many mechanisms contribute to the spread of antimicrobial-resistant genes, and integrons play a key role in this process. The aim of this study was to describe the serotypes and resistance profiles, and to characterize the presence of integrons in Salmonella strains isolated from Dourados, Mato Grosso do Sul, Brazil. Methodology: Thirty-six isolates from different sources were used. To evaluate the resistance profiles, the determination of minimum inhibitory concentrations together with polymerase chain reaction were used to screen for the presence of class 1 and class 2 integrons. Results: The Infantis serotype of Salmonella was the most frequently isolated serotype. Minimum inhibitory concentrations showed that out of the 36 isolates, 11 (30.5%) were resistant to all the antimicrobials tested. These resistant isolates were separated into three groups: 4 clinical isolates (36.4%), 3 food isolates (36.4%), and 4 water isolates (27.2%). Class 1 integrons occurred in 31 (86.1%) isolates and were found in all 11 resistant isolates (35.5 %) and in 20 (64.5%) of the non-resistant isolates. Class 2 integrons were found in 3 (8.3%) isolates, which were all non-resistant. Conclusion: The presence of an integron did not necessarily confer resistance. Future studies will seek to identify the mechanism behind integron-mediated antimicrobial resistance.